2023
DOI: 10.3390/ijms24119239
|View full text |Cite
|
Sign up to set email alerts
|

MiR-182-5p Is Upregulated in Hepatic Tissues from a Diet-Induced NAFLD/NASH/HCC C57BL/6J Mouse Model and Modulates Cyld and Foxo1 Expression

Abstract: Non-alcoholic fatty liver disease (NAFLD) is considered a relevant liver chronic disease. Variable percentages of NAFLD cases progress from steatosis to steatohepatitis (NASH), cirrhosis and, eventually, hepatocellular carcinoma (HCC). In this study, we aimed to deepen our understanding of expression levels and functional relationships between miR-182-5p and Cyld-Foxo1 in hepatic tissues from C57BL/6J mouse models of diet-induced NAFL/NASH/HCC progression. A miR-182-5p increase was detected early in livers as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Conversely, upregulated miR-483-5p inhibits cell proliferation and fibrosis by targeting PPARα and TIMP2 [34]. Other miRNAs in our results that might modulate cell proliferation in HBV-HCC include miR-874-3p [141], miR-451a [142][143][144][145][146][147], miR-182-5p [148][149][150][151][152][153], miR-98-5p [154][155][156][157][158], miR-363-3p [159][160][161][162] and miR-339-3p [163][164][165].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, upregulated miR-483-5p inhibits cell proliferation and fibrosis by targeting PPARα and TIMP2 [34]. Other miRNAs in our results that might modulate cell proliferation in HBV-HCC include miR-874-3p [141], miR-451a [142][143][144][145][146][147], miR-182-5p [148][149][150][151][152][153], miR-98-5p [154][155][156][157][158], miR-363-3p [159][160][161][162] and miR-339-3p [163][164][165].…”
Section: Discussionmentioning
confidence: 99%
“…Cultured human islets have increased levels of miRNA-146 in response to pro-inflammatory cytokines exposure decreased levels after high glucose exposure and interestingly stable levels after palmitate exposure [164]. Apart from the regulation of inflammatory response, miRNA-146 and miRNA 182-5p have also been involved in the reduction of cytoplasmic accumulation of lipids and cellular inflammatory response [165,166]. β-cell lines exposed to stearic acid and palmitic acid exhibit reduced expression of miRNA-297b-5p whereas the increased miRNA-297b-5p levels help to minimize apoptosis induced by stearic acid but also result in reduced insulin concentration [161].…”
Section: Micrornas Regulation By Lipid Accumulation In β Cellsmentioning
confidence: 99%
“…Likewise, research conducted by Rodrigues et al revealed that miR-21 acts as a crucial instigator of the whole-spectrum MASLD advancement and assumes an equally significant part in the evolution of MASLD to HCC [ 52 ]. It is worth mentioning that several miRNAs are differentially expressed in the transitions from MASLD to MASH to HCC, with some being overexpressed in tumors (miR-155, miR-193b, miR-182) while others are downregulated in HCC (miR-20a, miR-200c, miR-483) [ 53 , 54 , 55 ].…”
Section: Masld-induced Hccmentioning
confidence: 99%